Pelatihan Manajemen Umkm Dalam Rangka Peningkatan Wirausaha Di Delitua - Chon Cho Reynols Manday; Nani Sri Rezeki; Supriadi Siagian (CV. Armas Suan Sejahtera, 2025)
This study aims to analyze the effectiveness of MSME management training in enhancing entrepreneurship among micro, small, and medium enterprise actors. The MSME sector plays a crucial role in the national economy but often faces managerial challenges that affect business sustainability and innovation capacity. This research employs a qualitative approach through a case study of MSME groups that have participated in management training programs. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that comprehensive management training—covering strategic planning, financial management, digital marketing, and human resource management—significantly improves participants’ managerial knowledge and skills. These improved skills positively correlate with entrepreneurial development, reflected in the ability to identify new market opportunities, take calculated risks, and implement product or service innovations. These findings highlight the importance of structured and continuous training programs as catalysts for MSME development and the creation of resilient new entrepreneurs